Corporate Social Responsibility in the Age of Artificial Intelligence - Oana-Cristina MOGOȘ (Journal of Emerging Trends in Marketing and Management)
The present paper aims to determine the main impact of artificial intelligence (AI) tools and practices on corporate social responsibility (CSR). The center of the interest of the study is how emerging technologies have an influence on areas such as environment, society (health, education, smart cities and peace, justice, and strong institutions) and economy. The study shed light on the influence of artificial intelligence to corporate social responsibility actions by optimizing resources, enhancing access to services that are essential for living, and facilitating sustainable innovation. For this purpose, a literature review and a secondary data analysis were involved. At the same time, the paper is also approaching the topic of the risks of AI implementation. Among this, the study presents the privacy threats, cybersecurity or the ethical dilemmas in relation with the use of data.